Effects of bipolar disorder on maternal and fetal health during pregnancy: a systematic review - Malak A. Mohamed; Abdulrahman Elhelbawy; Maria Khalid; Latifa A. AbdAllatif; Hagar E. Lialy (BMC, 2023)
Abstract Background Bipolar disorder (BD) is a mental disorder characterized by mood shifts from severe depression to mania. Pregnant women with BD may experience manic or depressive episodes, so they are usually concerned about the effects of BD on their pregnancy. The aim of this systematic review is to determine the effects of BD on maternal health and fetal health, weight, and development. It also addresses how BD affects the probability of incidence of pregnancy complications in women with bipolar compared with healthy controls. Methods Seven electronic databases (Ovid MEDLINE, Embase, MIDRIS, APA PsychINFO, Scopus, Web of Science, and ScienceOpen) were searched, and 1728 eligible studies were identified. After deduplication, screening, and manual search processes, we included only 15 studies. Descriptive analysis, and calculation of the probability of incidence for each pregnancy outcome were used to analyze the results. Results The findings of the included studies suggest that BD during pregnancy may affect both fetal growth and maternal health by increasing the risk of giving birth to an infant with some birth defects such as microcephaly, CNS problems, small for gestational age, and other congenital anomalies, in addition to causing some obstetric complications such as gestational hypertension, preterm labor, need for assisted delivery, hospital readmission, and others. Conclusion Bipolar disorder during pregnancy negatively affects mothers and their fetuses and increases the probability of incidence of obstetrics complications.